Community Empowerment Through Ecoprint Training in the “One Day for One Happiness” Program - Sulaeman Fityan Saputra; Bagas Firzi Firmansyah; Radivan Bagas Kusuma; Nining Hardiyanti; Fathiril Haq (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: This study aims to describe the process of community empowerment through ecoprint training as a strategy for capacity building and the development of economic self-reliance in Jatijajar Village. Methodology: This study employs a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation, with source and technique triangulation used to ensure data validity. Data were analyzed through data collection, reduction, presentation, and conclusion drawing. The empowerment process consists of three stages: awareness, capacity transformation, and skill enhancement. Results: The findings show that ecoprint training improved participants’ technical skills, self-confidence, creativity, collaboration, and decision-making participation. Of 30 participants, 24 (80%) could produce acceptable ecoprint products independently, while 18 (60%) developed their own patterns and product variations. Conclusions: Ecoprint training can be viewed as a practical and sustainable model of community empowerment that contributes to the development of economic self-reliance through the growth of the creative economy in rural areas. Limitations: This study is limited to the “One Day for One Happiness” program. Contributions: This study makes a conceptual and practical contribution to a creative skills-based empowerment model that can be replicated in other rural areas. Thus, ecoprint training is viewed not merely as an artistic activity, but as a community development strategy rooted in local potential and focused on economic self-reliance and social sustainability.